Principia ethica - "Moore, G.E" (Mineola, 2004)
This volume revolutionized philosophy and forever altered the direction of ethical studies. It clarifies some of moral philosophy's most common confusions and redefines the science's terminology. 6 chapters explore: the subject matter of ethics, naturalistic ethics, hedonism, metaphysical ethics, ethics in relation to conduct, and the ideal.
Keywords: Ethics